Productivity and partial budget analysis in wheat-rice sequences as influenced by integrated plant nutrition system and legume crops inclusion (Bangladesh Journal of Agricultural Research, 2016)
The experiments were carried out at the Regional Wheat Research Centre, Rajshahi of Bangladesh Agricultural Research Institute (BARI) for two consecutive years, 2009-10 and 2010-11 to evaluate the agro-economic productivity of Wheat-Rice cropping sequence as influenced by integrated plant nutrition system (IPNS) and inclusion of legume crops. The experiment comprised of four cropping sequences viz. Wheat-Mungbean- T. Aman rice, Wheat-Blackgram- T. Aman rice, Wheat-Sesbania- T. Aman rice and Wheat- Fallow- T. Aman rice; and six nutrient treatments viz. 100% recommended nutrient rates, IPNS with 3 t ha-1 poultry manure (PM), IPNS with 6 t ha-1 PM, IPNS with 5 t ha-1 cowdung (CD), IPNS with 10 t ha-1 CD and farmers practice (FP). It was carried out in a split-plot design assigning cropping sequences in the main plots and nutrient treatments in the sub-plots with three replications. For the IPNS, the 100% nutrient rates were adjusted with manure and fertilizers. Inclusion of mungbean in the Wheat-Rice cropping sequence showed higher production cost but it gave higher system productivity, gross return, gross margin, benefitcost ratio and production efficiency. This cropping sequence gave on an average 57% higher wheat equivalent yield (WEY) compared to the existing Wheat-Rice sequence followed by blackgram included cropping sequence. The IPNS based fertilizer and manure application had better yield performance, WEY, gross margin, gross return, benefit-cost ratio, production efficiency and land use efficiency as compared to 100% chemical fertilizers or FP. It is concluded that the Wheat-Mungbean-Rice cropping sequence with IPNS approach is a productive and profitable technology for crop cultivation.Bangladesh J. Agril. Res. 41(1): 17-39, March 2016